A method for preparing a particle size restructured PE plastic standard sample
Through particle size recombination and heating and cooling treatment, a standard plastic sample with uniform and dense internals was prepared, which solved the problems of complex preparation process and high threshold in the prior art, and achieved the effect of simple operation and low cost.
Patent Information
- Application Number
- CN202411275253.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-09-12
AI Technical Summary
In the prior art, the preparation process of plastic standard samples is complex and has a high threshold, making it difficult to meet the needs of simple operation and low cost.
The preparation method of particle size recombinant PE plastic standard sample is adopted. By mixing PE plastic particles of different particle sizes in a certain proportion, adding lead and cadmium standard solutions, drying, pressing and heating and cooling are carried out to prepare plastic standard sample with uniform and dense interiors.
It realizes the uniform and dense interior of the plastic standard sample, which is easy to operate, low cost, and does not require complex instruments and equipment, and can meet the needs of daily qualitative and semi-quantitative analysis of XRF.
Smart Images

Figure CN118858341B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of spectral analysis, and more particularly to a method for preparing a particle size restructured PE plastic standard sample. Background Art
[0002] X-ray fluorescence spectroscopy, also known as X-ray fluorescence spectrometry (XRF), is an important elemental analysis and compound structure analysis technology. It is suitable for qualitative and quantitative analysis of multiple elements in various samples such as plastics, metals, ores, liquids, soils and other materials without damaging the samples. Sample preparation is a very important link in XRF testing. Powder pressing and melting sample preparation are the main sample preparation methods for solid samples used in XRF testing. Among them, the powder pressing method is relatively simple and more suitable for the determination of volatile elements, but the particle size effect is obvious; the test piece obtained by the melting sample preparation method has good uniformity and can better eliminate the influence of matrix effect and particle size effect on the test results, but the operation is complicated and requires special equipment.
[0003] In order to obtain more accurate data, XRF testing requires a standard sample that matches the sample matrix and has a uniform distribution of target components as a reference. However, the types of standard sample matrices currently available on the market are limited, and the types and concentrations of elements contained in them are fixed, while customizing standard samples with specific matrices, element types and concentration gradients is relatively expensive. Some analysts also make their own standard samples for specific samples. For example, Xu Jianping et al. used lithium tetraborate to pre-oxidize and melt sample preparation, and made manganese silicon alloy and ferromanganese standard materials into glass sheet standard samples to achieve XRF determination of silicon, manganese and phosphorus content in ferromanganese and manganese silicon alloy; Liu Xiaoli et al. used polyethylene as the substrate and used the melt pressing sample preparation process to prepare standard samples containing five elements of lead, cadmium, chromium, mercury and bromine with a certain concentration gradient for XRF ROHS sample analysis. Self-made standard samples can flexibly add standard substances and adjust the concentration gradient at any time. Combined with the advantages of XRF non-destructive and rapid detection, it can better facilitate the work of analysts.
[0004] Plastic standard samples have a wide range of applications and stable properties, and are the most common XRF standard samples. They are usually made by melting plastic raw materials → adding target elements → injection molding → tableting → demoulding and cutting. However, due to the complex process, the production threshold is relatively high.
[0005] Therefore, how to develop a plastic standard sample with simple preparation method and operation is an urgent problem to be solved by technicians in this field. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a method for preparing a particle size reconstituted PE plastic standard sample to solve the deficiencies in the prior art.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A method for preparing a particle size reconstituted PE plastic standard sample comprises the following steps:
[0009] (1) Adding lead and cadmium standard solutions to PE plastic particles, then adding water and mixing to obtain a mixed sample;
[0010] (2) drying the mixture and mixing it to obtain a dried sample;
[0011] (3) pressing the dried sample to obtain a pressed sample;
[0012] (4) The pressed sample is heated and cooled naturally to obtain a particle size reconstituted PE plastic standard sample.
[0013] Furthermore, in the above step (1), the PE plastic microparticles are prepared by mixing three types of PE plastic microparticles having particle sizes of 100 mesh, 300 mesh and 500 mesh in a mass ratio of 7:1:2.
[0014] Furthermore, in the above step (1), the mass concentration of lead and cadmium standard solutions is 1000 mg·L -1 .
[0015] Furthermore, in the above step (1), the mass volume ratio of PE plastic particles and lead and cadmium standard solutions is 5g:(0.1-1)mL, preferably 5g:0.5mL.
[0016] Furthermore, in the above step (1), the mixing device is a tumble mixer with a rotation speed of 80 to 100 r / min, preferably 100 r / min, and a mixing time of 10 to 15 min, preferably 10 min.
[0017] Furthermore, in the above step (2), the drying equipment is an oven, and the temperature is 75-95°C, preferably 75°C.
[0018] Furthermore, in the above step (3), the pressing device is a metal mold, the pressure is 30 MPa, and the time is 20 to 40 seconds, preferably 20 seconds.
[0019] Furthermore, in the above step (4), the heating device is an oven, the temperature is 135-145° C., preferably 145° C., and the time is 10-15 min, preferably 10 min.
[0020] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:
[0021] The invention applies the dense packing theory, mixes PE plastic particles of different particle sizes in a certain proportion, adds a standard, and then prepares a PE plastic standard sample by a method of tabletting, heating and melting, and cooling and forming. The sample has the characteristics of internal uniformity and density, and the data is stable when placed at room temperature for 6 months, which can meet the daily qualitative and semi-quantitative analysis of XRF. The preparation method is simple, the cost is low, and no complicated instruments and equipment are required, which provides a new idea for homemade standard samples in the laboratory. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The appearance and surface photos of the four samples are shown below;
[0023] Figure 2 XRD diagrams of plastic particles before and after melting (A: 100 mesh powder; B: 100 mesh powder after melting; C: particle size reorganized powder; D: particle size reorganized powder after melting);
[0024] Figure 3 XRD patterns of four samples (E: 100 mesh sample; F: 300 mesh sample; G: 500 mesh sample; H: particle size reorganization sample);
[0025] Figure 4 DSC melting curves of four samples;
[0026] Figure 5 The infrared spectra of the four samples (1500~1400cm -1 ). DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] The method for preparing a particle size restructured PE plastic standard sample comprises the following steps:
[0030] (1) Weigh 3.5 g of 100-mesh PE plastic microparticles, 0.5 g of 300-mesh PE plastic microparticles, and 1 g of 500-mesh PE plastic microparticles in a glass test tube, mix them, and add 0.5 mL of 1000 mg / L -1 The lead and cadmium standard solutions were prepared by adding water to a total volume of 25 mL. After tightening the cap of the glass test tube, the glass test tube was placed in a flip mixer and mixed at a speed of 100 r / min for 10 min to obtain a mixed sample.
[0031] (2) Transfer the mixed sample to a beaker, place it in an oven, dry it at 75°C, and mix it to obtain a dried sample;
[0032] (3) Weigh 0.5 g of the dried sample and place it in a metal mold, and press it at 30 MPa for 20 seconds to obtain a pressed sample;
[0033] (4) Place the pressed sample on a clean glass plate and put it into an oven. Heat it at 145°C for 10 min and cool it naturally to obtain a particle size reconstituted PE plastic standard sample.
[0034] Example 2
[0035] The method for preparing a particle size restructured PE plastic standard sample comprises the following steps:
[0036] (1) Weigh 3.5 g of 100-mesh PE plastic microparticles, 0.5 g of 300-mesh PE plastic microparticles, and 1 g of 500-mesh PE plastic microparticles in a glass test tube, mix them, and add 0.1 mL of 1000 mg / L -1 The lead and cadmium standard solutions were prepared by adding water to a total volume of 25 mL. After tightening the cap of the glass test tube, the glass test tube was placed in a flip mixer and mixed at a speed of 100 r / min for 10 min to obtain a mixed sample.
[0037] (2) Transfer the mixed sample to a beaker, place it in an oven, dry it at 75°C, mix it well, and obtain a dried sample;
[0038] (3) Weigh 0.5 g of the dried sample and place it in a metal mold, and press it at 30 MPa for 20 seconds to obtain a pressed sample;
[0039] (4) Place the pressed sample on a clean glass plate and put it into an oven. Heat it at 145°C for 10 min and cool it naturally to obtain a particle size reconstituted PE plastic standard sample.
[0040] Example 3
[0041] The method for preparing a particle size restructured PE plastic standard sample comprises the following steps:
[0042] (1) Weigh 3.5 g of 100-mesh PE plastic microparticles, 0.5 g of 300-mesh PE plastic microparticles, and 1 g of 500-mesh PE plastic microparticles in a glass test tube, mix them, and add 0.1 mL of 1000 mg / L -1The lead and cadmium standard solutions were added with water to a total volume of 10 mL. After tightening the cap of the glass test tube, the glass test tube was placed in a flip mixer and mixed at a speed of 80 r / min for 10 min to obtain a mixed sample.
[0043] (2) Transfer the mixed sample to a beaker, place it in an oven, dry it at 85°C, mix it well, and obtain a dried sample;
[0044] (3) Weigh 0.5 g of the dried sample and place it in a metal mold, and press it at 30 MPa for 30 seconds to obtain a pressed sample;
[0045] (4) Place the pressed sample on a clean glass plate and put it into an oven. Heat it at 135°C for 12 minutes and cool it naturally to obtain a particle size reconstituted PE plastic standard sample.
[0046] Example 4
[0047] The method for preparing a particle size restructured PE plastic standard sample comprises the following steps:
[0048] (1) Weigh 3.5 g of 100-mesh PE plastic microparticles, 0.5 g of 300-mesh PE plastic microparticles, and 1 g of 500-mesh PE plastic microparticles in a glass test tube, mix them, and add 1 mL of 1000 mg / L -1 The lead and cadmium standard solutions were prepared by adding water to a total volume of 25 mL. After tightening the cap of the glass test tube, the glass test tube was placed in a flip mixer and mixed at a speed of 100 r / min for 15 min to obtain a mixed sample.
[0049] (2) Transfer the mixed sample to a beaker, place it in an oven, dry it at 95°C, and mix it to obtain a dried sample;
[0050] (3) Weigh 0.5 g of the dried sample and place it in a metal mold, and press it at 30 MPa for 40 seconds to obtain a pressed sample;
[0051] (4) Place the pressed sample on a clean glass plate and put it into an oven. Heat it at 140°C for 15 minutes and cool it naturally to obtain a particle size reconstituted PE plastic standard sample.
[0052] Performance Testing
[0053] Abstract: In this paper, polyethylene (PE) plastic particles are used as raw materials. Based on the principle of dense stacking, the particle size reorganization method is used to mix PE plastic particles of different particle sizes in proportion, add lead and cadmium elements, and then press and melt to obtain plastic standard samples. The samples are tested for uniformity and stability, and microwave digestion and plasma emission spectrometry are used for value determination. The results show that the samples obtained after particle size reorganization are dense inside, the target elements are evenly distributed, and the data are stable after being placed at 20°C for 6 months. This method omits the complicated melting and pressing steps, and the operation is simple and easy. The obtained plastic standard samples can meet the daily analysis of XRF.
[0054] Keywords: PE plastic, plastic standard sample, dense stacking principle, XRF
[0055] 1 Experimental part
[0056] 1.1 Main raw materials
[0057] Lead and cadmium standard solutions, mass concentrations are 1000 mg·L -1 .
[0058] High-density polyethylene (PE-HD) plastic microparticles, 100 mesh / 300 mesh / 500 mesh, commercially available.
[0059] The test water is first-grade water.
[0060] 1.2 Main equipment and instruments
[0061] Differential scanning calorimeter (DSC), METTLER TOLEDO DSC1; XGT-5200WR X-ray fluorescence spectrometer (XRF); D8 Focus X-ray diffractometer (XRD); Thermo Nico LET iS10 Fourier transform infrared spectrometer (FTIR) equipped with SMART ATR component (with OMNIC 9.8 software) and tablet press; oven; tumble mixer; Wanhao VMS-2515H optical image measuring instrument.
[0062] 1.3 Sample preparation (i.e. Example 1)
[0063] The particle size effect of the samples obtained by the powder tableting method is obvious. This is because the powder is not densely packed and there are many pores, which will affect the stability and uniformity of the XRF measured data. The melting sample preparation method can obtain relatively dense samples, but if the mold is not pressurized, there may be bubbles inside the sample, which will also affect the uniformity of the prepared test piece. Therefore, this work takes three kinds of PE plastic particles, coarse (100 mesh), medium (300 mesh), and fine (500 mesh), and mixes them in a mass ratio of 7:1:2. First, a relatively dense sample is prepared by the powder tableting method, and then the sample is heated to melt it to improve the effect of the non-pressurized melting sample preparation method.
[0064] 1.3.1 Preparation of spiked PE plastic microparticles
[0065] Weigh 5 g of PE plastic microparticles in a glass test tube and add 0.5 mL of 1000 mg / L -1 100 mL of lead and cadmium standard solution, and then add first-grade water to make the total volume 25 mL. After tightening the bottle cap, place the test tube in a flip mixer and mix at a speed of 100 r / min for 10 minutes. Transfer the mixture to a beaker, place it in an oven, and dry it at 75°C. Mix the dried sample and set it aside.
[0066] 1.3.2 Preparation of standard samples
[0067] Weigh 0.5g of the sample prepared according to "1.3.1", place it in a metal mold, and maintain the pressure at 30MPa for 20s. Immediately place the pressed sample on a clean glass plate and put it in an oven, stand at 145℃ for 10min, and then cool naturally.
[0068] 1.4 Performance testing and result representation
[0069] 1.4.1XRD test
[0070] Cu Kα line, using continuous scanning mode, working voltage 40KV, current 40mA, scanning range 5°~75°, step length 0.5° / step, scanning speed 0.5s / step.
[0071] 1.4.2XRF test
[0072] SDD silicon drift detector, X-ray tube voltage 4~50kV, Rh rhodium target end window, resolution 170keV, 5-element filter (Cd / Pb / Cr / Hg / Br).
[0073] 1.4.3DSC determination
[0074] Temperature calibration and thermal power calibration of metal indium and metal tin were performed before use. 10 mg of sample was taken each time and the temperature was increased from 0°C to 170°C at a rate of 10°C / min.
[0075] 1.4.4 FTIR determination
[0076] Scanning was performed in ATR mode, with a reflective crystal of ZnSe, an incident angle of 45°, 32 scans, and a scanning range of 700 to 4000 cm -1 , resolution 0.5cm -1 .
[0077] 2 Results and discussion
[0078] 2.1 Surface morphology of different PE plastic standard samples
[0079] Samples were prepared using 100 mesh, 300 mesh, 500 mesh and recombined PE plastic particles, and photographed using an image measuring instrument. The results are as follows Figure 1 shown.
[0080] Depend on Figure 1 It can be seen that the samples obtained after the melting of the four PE plastic particles are significantly different. Among them, the particle size of the 100-mesh sample is reduced, the height is increased, and its surface is rough. There are obvious pores left after the particles are melted and agglomerated. The particle size of the 300-mesh sample did not change much, the height was slightly reduced, the top became rounded, and there were also uneven pores on the surface. The 500-mesh sample had a large deformation, a larger particle size, and obvious collapse. The particle size reorganization sample basically maintained a regular disc shape, but the height was reduced, and its surface was as uniform and dense as the 500-mesh sample. In order to understand the reasons for the morphological differences in the four samples, the crystallization behavior and crystallization morphology of the four samples were explored with the help of XRF, DSC and infrared spectrometers.
[0081] 2.2 XRD patterns of PE plastic particles and samples
[0082] PE is a typical partially crystalline polymer with three characteristic peaks on its XRD spectrum, at 2θ=19.5°, 21.6° and 24.0°, representing the diffraction peaks of the amorphous region and the (110) and (200) crystal planes of the orthorhombic phase, respectively. The polyethylene molecular chains are orderly arranged in parallel in the crystalline region, while they are entangled and randomly arranged in the amorphous region. The intensity of the two crystal plane diffraction peaks is 110 and I 200 Proportional to the degree of crystallinity.
[0083] Depend on Figure 2 It can be seen that the amorphous peak at 2θ=19.5° in the samples made of the two PE plastic particles decreased significantly, indicating that there are fewer disordered polyethylene molecular chains in the samples. 110 and I 200 It becomes stronger and the peak shape is sharper, which means that the process of polyethylene in the state of plastic particles melting and then solidifying again makes the arrangement of crystals more regular and orderly, thereby improving the crystallinity.
[0084] Depend on Figure 3 It can be seen that by comparing the XRD patterns of the four samples, it is found that the characteristic peaks (I 110 and I 200 ) are similar in strength, but are significantly greater than the 500-mesh sample, which means that the crystallinity of the 500-mesh sample is lower than that of the other samples.
[0085] 2.3 DSC and IR spectroscopy analysis of samples
[0086] The DSC melting curves of four samples were tested and the results are as follows: Figure 4 shown.
[0087] Depend on Figure 4 It can be seen that from 100 mesh to 500 mesh, the melting point of the sample decreases as the particle size of PEPE plastic particles decreases, and the peak shape changes from flat and wide to narrow and sharp. However, while the melting point of the particle size reorganized sample has rebounded, the peak shape also has the characteristics of narrow and sharp. Polyethylene is a crystalline polymer, and its melting temperature is related to the thickness of the chip. The smaller the chip thickness, the lower the melting temperature. In addition, under the same experimental conditions, the wider the thickness distribution of the crystalline chip, the wider the melting temperature range, which is manifested as a wider melting peak on the DSC curve. Combined with Figure 1 It is speculated that when the 100-mesh and 300-mesh plastic particles are melted and recrystallized, the existence of pores (defects) causes the thickness distribution of the chips in the prepared samples to be wider, thus forming a relatively wider melting peak. The pores of the 100-mesh sample are larger and more obvious, so the melting peak is the widest. The sample made of 500-mesh particles has the narrowest melting peak and the lowest melting temperature, indicating that the chip thickness in the 500-mesh sample is smaller and more uniform, but the sample is also easier to deform. While maintaining a narrow melting peak, the melting temperature of the particle size reorganized sample is also higher than that of the 500-mesh sample. It is proved that after the plastic particles are densely stacked by using particle size reorganization, the pores are filled to the maximum extent, and the resulting crystallized chips have the effect of large thickness and uniformity.
[0088] The melting enthalpy ΔH can be obtained by integrating the melting peak and calculating the area. f . Crystallinity x c The calculation formula is as follows: In the formula, ΔH f The measured melting enthalpy ΔH of the sample f100% The melting enthalpy of HDPE when it is completely crystallized is 293 J / g. The calculated crystallinity results of the four samples are shown in Table 1.
[0089] In order to further verify the crystallinity data obtained by DSC method, the infrared spectra of four samples were scanned. The results are as follows Figure 5 shown.
[0090] According to Zerbi's conclusion, the mass percentage of amorphous part in the polymer of orthorhombic n-alkane is x a Can pass 1473~1463cm -1 The intensity of the nearby double peaks is calculated using the formula: Therefore, the crystallinity formula is In the formula, I a and I b 1473cm respectively -1 and 1463cm -1The calculation results are also shown in Table 1.
[0091] Table 1 Crystallinity calculated by DSC and FTIR
[0092]
[0093] As shown in Table 1, although the value of crystallinity calculated by infrared spectroscopy is somewhat different from that obtained by DSC method, the trend of the change of the values is consistent. Combined with the XRD test results and density data, the following conclusions can be drawn: the smaller the particle size of the plastic particles, the higher the density of the sample formed after melting, the lower the crystallinity, and the more uniform the sample. However, through particle size reorganization, dense stacking is achieved by using PE plastic particles of different particle sizes to press the tablets, and the PE plastic standard sample formed after melting can have both high crystallinity and high density.
[0094] 2.4 Uniformity and stability test of particle size reconstructed samples
[0095] The signal intensities of Pb and Cd of the homemade particle size reconstructed samples were measured by XRF and data was collected. The uniformity and stability tests were carried out in accordance with GB / T 15000.3-2023 (Guidelines for Standard Samples Part 3: Standard Sample Value Determination and Uniformity and Stability Evaluation).
[0096] 2.4.1 Uniformity test
[0097] Two concentration levels (i.e., Example 1 and Example 2) were selected from the prepared particle size recombinant samples, and 15 samples were randomly selected for each test. Each sample was tested 3 times under repeated conditions. All repeated tests of the samples were carried out in a random order, and 15 groups of 45 sample test data were obtained for each concentration level. The uniformity of the standard sample was tested by one-way analysis of variance, with a significance level of α = 0.05. If the statistical value F < F 0.05(15,3) , then it is considered that there is no significant difference between groups and within groups, which means that the samples are uniform. The statistical value F is obtained using the following formula: In the formula, Q1 is the sum of squares of the deviations between groups, Q2 is the sum of squares of within-group deviations, m is the number of groups; n is the number of sample level tests in each group.
[0098] The results are shown in Table 2.
[0099] Table 2 Calculation of F value of particle size reorganization sample statistics
[0100]
[0101] From the uniformity test results in Table 2, it can be seen that the F values of Pb and Cd in the particle size reorganization samples with two addition levels are both less than F 0.05(15,3)=8.70, indicating that there was no significant difference between and within groups.
[0102] 2.4.2 Stability test
[0103] Stability is a measure of the ability of a standard sample to maintain its characteristic value within a specified range at a specific time interval and storage conditions. Take a particle size reconstituted sample with an addition level of Pb 20mg / kg and Cd 20mg / kg, set the storage condition to 20℃, and the time interval is 6 months. The monitoring intervals are 0, 0.5, 1, 2, 4, and 6 months, and 3 samples are randomly selected at each time point. Each sample is measured 3 times in parallel and the average value is taken. Evaluate the stability of the sample based on the measured data.
[0104] The results are shown in Table 3.
[0105] Table 3 Calculation data of stability test of particle size recombinant sample
[0106]
[0107]
[0108] In Table 3, b1 is the slope,
[0109] b0 is the intercept,
[0110] s 2 is the standard deviation of each point on the line, (n is the number of stability tests);
[0111] s(b1) is the uncertainty associated with the slope,
[0112] From Table 3, we can see that when the confidence level P = 0.95, |b1| in the sample < t (0.95,n-2) ×s(b1). This proves that there is no significant difference in the stability of the particle size reconstituted sample during the 6-month test period, and the particle size reconstituted sample is stable when stored at 20°C for 6 months.
[0113] 2.5 Determination and uncertainty of homemade particle size reconstructed samples
[0114] Microwave digestion was used to dissolve the sample, and the Pb and Cd contents in the particle size reconstructed samples were determined by ICP-OES. The determination results and uncertainties are shown in Table 4.
[0115] Table 4 Value data of particle size reconstructed samples (n=7)
[0116]
[0117] It can be seen from Table 4 that the standard relative uncertainty of the prepared particle size reconstruction samples is less than 5%, which can fully meet the qualitative and semi-quantitative analysis of XRF.
[0118] 3 Conclusion
[0119] This work applies the dense packing theory, mixes PE plastic particles of different particle sizes in a certain proportion, adds a standard, and then prepares PE plastic standard samples by pressing, heating and melting, and cooling to form. The samples prepared by this particle size reorganization method have the characteristics of internal uniformity and density, simple preparation, low cost, and no need for complex instruments and equipment. The uniformity of the prepared samples is good, and the data is stable after being placed at room temperature for 6 months, which can meet the daily qualitative and semi-quantitative analysis of XRF. This work provides a new idea for homemade standard samples in the laboratory.
[0120] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a particle size reconstituted PE plastic XRF standard sample, characterized in that: The specific steps include: (1) adding a lead standard solution and a cadmium standard solution to PE plastic particles, and then adding water, and mixing to obtain a mixed sample; The PE plastic particles are prepared by mixing three kinds of PE plastic particles with particle sizes of 100 mesh, 300 mesh and 500 mesh in a mass ratio of 7:1:2; (2) drying the mixture and mixing it to obtain a dried sample; (3) pressing the dried sample to obtain a pressed sample; (4) The pressed sample is heated to a temperature of 135-145° C. and cooled naturally to obtain the XRF standard sample of the reconstituted PE plastic of the particle size.
2. The method for preparing a particle size reconstituted PE plastic XRF standard sample according to claim 1, characterized in that: In step (1), the mass concentration of the lead standard solution and the cadmium standard solution are both 1000 mg·L -1 .
3. The method for preparing a particle size reconstituted PE plastic XRF standard sample according to claim 1, characterized in that: In step (1), the mass volume ratio of the PE plastic particles to the lead standard solution is 5g:(0.1-1)mL, and the mass volume ratio of the PE plastic particles to the cadmium standard solution is 5g:(0.1-1)mL.
4. The method for preparing a particle size reconstituted PE plastic XRF standard sample according to claim 1, characterized in that: In step (1), the mixing device is a tumble mixer with a rotation speed of 80 to 100 r / min and a mixing time of 10 to 15 min.
5. The method for preparing a particle size reconstituted PE plastic XRF standard sample according to claim 1, characterized in that: In step (2), the drying equipment is an oven at a temperature of 75 to 95°C.
6. The method for preparing a particle size reconstituted PE plastic XRF standard sample according to claim 1, characterized in that: In step (3), the pressing equipment is a metal mold, the pressure is 30 MPa, and the time is 20 to 40 seconds.
7. The method for preparing a particle size reconstituted PE plastic XRF standard sample according to claim 1, characterized in that: In step (4), the heating device is an oven and the heating time is 10 to 15 minutes.
Citation Information
Patent Citations
Method for preparing coated flux tablet for XRF cobalt internal standard analysis
CN108414556A
Grading method of high-purity superfine spherical powder
CN116553566A